Markov Chain Modeling for Router Hotspots on Network-On-Chip - Asrani, Lit; Nurdiani, Zamhari; N., Rajaae; Sharifah Masniah, Wan Masra; Kismet, Hong Ping (2011)
A Network-on-Chip (NoC) is a current paradigm in complicated System-on-Chip (SoC) designs that renders compe- tent on-chip communication architecture. It proposes scalable communication to SoC and grants decoupling of communi- cation and computation. In NoC, design space exploration is vital merited to trade-offs among latency, area, and power consumption. Therefore, analytic modeling is crucial step for early NoC design. This paper delivers a top-down approach router model, and employs this model for mesh NoC performance analysis quantified in terms of throughput, average of queue size, efficiency, loss and waiting time. As a case study, the advised model is applied to map a MPEG4 video core to a 4 × 4 mesh NoC with deterministic routing to evaluate the overall NoC quality of service (QoS). The model is utilized as well to acquaints how much occupancy of average queue size for each router that reduces resources (hardware) area and cost. The accuracy of our approach and its practical use is illustrated through extensive simulation results.